PENGARUH PROSEDUR, PENDIDIKAN, TEKANAN WAKTU, DAN ANGGARAN REVIU PADA KUALITAS REVIU LAPORAN KEUANGAN PEMERINTAH DAERAH - Widyarini, Komang; Ratnadi, Ni Made Dwi (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.05.NO.03.TAHUN 2016, 2016)
The purpose of this study are examine the effect of the review procedures, educational background, time pressure, and review funds budget on the quality review of the Local Government Finance Report. The population of this research was the Government Internal Supervisory Apparatus Inspectorate of Provincial/District/City in Bali which amounted to 171 people. The samples consisted 45 of people that were determined by purposive sampling technique. The data were analyzed using linear regression and data were collected by questionnaire. The analysis showed that the review procedures, educational background, and the review funds budget a positive effect on the quality review of local government financial reports. The time pressure affected in negatively on the quality review of local government financial reports. The pressure affected the result because of time constraints and the complexity of the task assignment higher then what it was expected. The regional Inspectorate optimize on assignments between budget time and complexity of the task in order to lower the risk and also  decrease in the quality of the review.
Keywords: review quality, review procedure, educational background, time pressure, budget funds review